DIAGNOSTIC SIGNIFICANCE OF IL-15 IN SJS/TEN SYNDROME (International journal of medical sciences, 2025)
tevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening severe cutaneous adverse reactions characterized by widespread epidermal and mucosal necrosis. Although clinical scoring systems such as SCORTEN play an important role in severity assessment, they have limited predictive value during early disease stages. Consequently, immunological biomarkers—including cytokines—are being actively investigated to improve early diagnostics and prognostication. Interleukin-15 (IL-15) has emerged as a potent activator of CD8⁺ T lymphocytes and NK cells, enhancing cytotoxic pathways and amplifying keratinocyte apoptosis. This paper reviews the role of IL-15 in SJS/TEN pathogenesis, its association with cytotoxic lymphocyte activity, and its diagnostic and prognostic significance.